Exercise Motivations, Barriers, and Preferences of Tahfiz Students: A Qualitative Study - Farah Wahida Ibrahim; Arimi Fitri Mat Ludin; Nur Aqilah Marzuki; Ismarulyusda Ishak; Mohd Sham Othman; Nor Malia Abd Warif; Mohd Zaharen Md. Zahir; Muhammad Toriq Yaacob (Makara Journal of Health Research, 2022)
Background: In Malaysia, the increasing prevalence of physical inactivity is alarming. The effects of adopting a sedentary lifestyle have led to health problems such as coronary heart disease and type II diabetes mellitus, as well as increased mortality rates. Young adults, including tahfiz students, tend to be physically inactive due to much time spent sitting during lectures or studying. Therefore, an active lifestyle must be encouraged. This study aims to identify the factors that influence tahfiz students to exercise.